A strategy for effective radioprotection by chitosan-based long-circulating nanocarriers1. Issue 15 (21st April 2015) - Zhou, Yuan; Hua, Song; Yu, Jiahua; Dong, Ping; Liu, Fenju; Hua, Daoben
<x xml:space="preserve">Abstract</x> Effective radioprotection is achieved by chitosan-based long-circulating nanocarriers with radioprotective agents. The stable encapsulation does not reduce its radioprotective capability and exhibits prolonged retention time, thereby showing more beneficial effects.